TLR5 variants are associated with the risk for COPD and NSCLC development, better overall survival of the NSCLC patients and increased chemosensitivity in the H1299 cell line - Baranašić, Jurica; Šutić, Maja; Catalano, Calogerina; Drpa, Gordana; Huhn, Stefanie; Majhen, Dragomira; Nestić, Davor; Kurtović, Matea; Rumora, Lada; Bosnar, Martina; Vukić Dugac, Andrea; Sokolović, Irena; et al. (Biomedicines, 2022)
Chronic obstructive pulmonary disease (COPD) is considered as the strongest independent risk factor for lung cancer (LC) development, suggesting an overlapping genetic background in both diseases. A common feature of both diseases is aberrant immunity in respiratory epithelia that is mainly regulated by Toll-like receptors (TLRs), key regulators of innate immunity. The function of the flagellin-sensing TLR5 in airway epithelia and pathophysiology of COPD and LC has remained elusive. We performed case-control genetic association and functional studies on the importance of TLR5 in COPD and LC development, comparing Caucasian COPD/LC patients (n = 974) and healthy donors (n = 1283). Association analysis of three single nucleotide polymorphisms (SNPs) (rs725084, rs2072493_N592S, and rs5744174_F616L) indicated the minor allele of rs2072493_N592S to be associated with increased risk for COPD (OR = 4.41, p < 0.0001) and NSCLC (OR = 5.17, p < 0.0001) development and non-small cell LC risk in the presence of COPD (OR = 1.75, p = 0.0031). The presence of minor alleles (rs5744174 and rs725084) in a co-dominant model was associated with overall survival in squamous cell LC patients. Functional analysis indicated that overexpression of the rs2072493_N592S allele affected the activation of NF-κB and AP-1, which could be attributed to impaired phosphorylation of p38 and ERK. Overexpression of TLR5N592S was associated with increased chemosensitivity in the H1299 cell line. Finally, genome-wide transcriptomic analysis on WI-38 and H1299 cells overexpressing TLR5WT or TLR5N592S, respectively, indicated the existence of different transcription profiles affecting several cellular pathways potentially associated with a dysregulated immune response. Our results suggest that TLR5 could be recognized as a potential biomarker for COPD and LC development with functional relevance.